Analysis of Bilinear Distillation Column Using Tubular Model - Ibrahim, Norazlin (2004)
All studies on distillation columns aim at improving the process so that it can be run effectively and efficiently to yield better quality product with lower energy consumption.A good working model is needed as a basis for controller design.Tubular Columns means a column represented by a spatially distributed model.It has been modeled using Partial Differential Equation numerically.The advantage of using Partial Differential Equation is that it can analyze more than one independent variable and produce the output in a natural way. Numerically,the solution that has been used in this study is pdepe command line function on the Tubular columns model for rectifier and stripper section.A continuous spatially distributed Tubular equations had been derived and validated using pdepe function in two space dimension h’ and τ.It depends on the sensitivity of right boundary condition, and two parameters α and h’.The open loop and closed loop test is done throughout this study, shows the comprehensively output of composition and separation.The Tubular model now, is ready to be applied on any type of control method.